Catalytic Asymmetric Michael Reaction of 5H‐Oxazol‐4‐Ones with α, β‐Unsaturated Acyl Imidazoles. Issue 48 (14th October 2015) - Zhang, Bangzhi; Han, Fengxia; Wang, Linqing; Li, Dan; Yang, Dongxu; Yang, Xiaoli; Yang, Junxian; Li, Xiaofang; Zhao, Depeng; Wang, Rui
Abstract: The asymmetric Michael reaction between 5 H ‐oxazol‐4‐ones and α, β‐unsaturated acyl imidazoles is reported. A novel 2‐benzo[ b ]thiophenyl‐modified chiral ProPhenol species is synthesized and used as a ligand, leading to good enantioselectivities in this asymmetric conjugate addition reaction. Furthermore, the introduction of phenol additives as achiral co‐ligands is found to improve the reaction's chemical yields, diastereoselectivities, and enantioselectivities. Abstract : Is that your phenol answer? The asymmetric Michael reaction between 5 H ‐oxazol‐4‐ones and α, β‐unsaturated acyl imidazoles is realized by utilizing a dinuclear zinc complex catalyst. The introduction of phenol additive as an achiral co‐ligand is found to improve the reaction's chemical yields, diastereoselectivities, and enantioselectivities.